2014
DOI: 10.1186/s12887-014-0303-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and breathing in premature infants at 6 months post-natal age

Abstract: BackgroundPoor sleep contributes to the developmental problems seen in preterm infants. We evaluated sleep problems in preterm infants 6 months of post-gestational age using the subjective Brief Infant Sleep Questionnaire (BISQ) and objective sleep tests. We also compared the sleep of premature infants with that of full-term infants.MethodsThe study included 68 6-month-old full-term healthy infants and 191 premature infants born at <37 weeks gestation. All parents completed the BISQ-Chinese version and sleep d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 27 publications
5
51
0
Order By: Relevance
“…Preterm children are also at risk for more sleep disruption and sleep disorders such as OSAS. 13, 143 …”
Section: Discussionmentioning
confidence: 99%
“…Preterm children are also at risk for more sleep disruption and sleep disorders such as OSAS. 13, 143 …”
Section: Discussionmentioning
confidence: 99%
“…Longer nocturnal sleep duration, more night awakenings, and longer daytime sleep duration was also observed in 6‐month‐old infants born at an older age (31.5 ± 3.2 weeks GA, 1467 ± 588.6 g, mean±SD) compared to term control infants (Huang et al . ). The authors of this study did not evaluate neurodevelopmental disabilities, but did note that sleep disturbances were associated with respiratory problems (Huang et al .…”
Section: Introductionmentioning
confidence: 97%
“…The authors of this study did not evaluate neurodevelopmental disabilities, but did note that sleep disturbances were associated with respiratory problems (Huang et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Preterm birth has been associated with an increased prevalence of later physical and mental morbidities and neurodevelopmental disabilities and the risk increases with decreasing gestational age (GA) and birthweight (BW) . Prematurely born children have also been reported to be at increased risk of sleep problems like nocturnal and early morning awakening , disturbed sleep due to sleep‐related breathing disorders and maybe the phenomenon known as advanced sleep phase . Not all previous studies have shown worse sleep outcomes among premature born children.…”
Section: Introductionmentioning
confidence: 99%